IDDF2020-ABS-0223 An analysis of adverse effects of thalidomide treatment in inflammatory bowel disease with peripheral neuritis. (18th November 2020) - Peng, Xiang; Yao, Jiayin; Deng, Jun
Abstract : Background: Thalidomide has been gradually recognized in the treatment of IBD because of its anti-angiogenesis and immunomodulatory effect. The safety and adverse reactions of thalidomide have also attracted considerable attention. This study aims to analyze the peripheral neuropathy associated with thalidomide in IBD and to provide guidance for safe use. Methods: We analyse 176 patients with IBD. They have suffered from peripheral neuritis due to thalidomide treatment. The peripheral nerve symptoms were evaluated, the electromyography was performed, and the dose-effect relationship of neurotoxicity was analyzed. Results: 70 patients had symmetrical numbness of hand or foot, of which 57 had abnormal electromyogram. 51.8% (55/106) of the patients without peripheral nerve symptoms still had abnormal electromyogram. Abnormal electromyogram usually occurred at 15 months in patients with clinical symptoms, which was significantly earlier than that in asymptomatic patients (15.4±16.36 vs 21.63±16.27, P=0.016). In patients with an abnormal electromyogram, the daily dose was 0.084±0.023, the cumulative use time was 19.22±16.6 months, and the cumulative dose was 65.26±90.99 g, while in patients with a normal electromyogram, the daily dose was 0.080±0.021 g, the cumulative use time was 19.63 ±16.4 months, and the cumulative dose was 51.5 ±124.84 g. There was no significant difference between the two groups. Peripheral neuropathy may occur earlier in males than in females, but no significance (36.1 ±96.9 vs 72.9 ±118.0 g, P=0.07, and 20.0±20.1 months, P=0.18). Conclusions: Whether thalidomide can lead to peripheral neuritis has a large individual difference. Male is more likely to develop peripheral neuritis than female to develop peripheral neuritis. But there is no statistical difference. Although symptomatic patients develop electromyogram damage earlier, it should be noted that there are still some patients with peripheral neuritis in asymptomatic patients. Therefore, electromyography should be monitored regularly in IBD patients with thalidomide for more than one year to avoid irreversible peripheral neuritis.